2001
DOI: 10.1099/0022-1317-82-6-1503
|View full text |Cite
|
Sign up to set email alerts
|

Visualization by atomic force microscopy of tobacco mosaic virus movement protein–RNA complexes formed in vitro

Abstract: The structure of complexes formed in vitro by tobacco mosaic virus (TMV)-coded movement protein (MP) with TMV RNA and short (890 nt) synthetic RNA transcripts was visualized by atomic force microscopy on a mica surface. MP molecules were found to be distributed along the chain of RNA and the structure of MP-RNA complexes depended on the molar MP : RNA ratios at which the complexes were formed. A rise in the molar MP : TMV RNA ratio from 20 : 1 to 60-100 : 1 resulted in an increase in the density of the MP pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Like other plant viruses, TMV encodes a movement protein (MP) that interacts with Pd and facilitates the intercellular passage of its genome (28,39,64). The MP modulates the size-exclusion limit (SEL) of the Pd (107) and also binds single-stranded nucleic acids in vitro to form an unfolded, elongated ribonucleoprotein complex with apparent dimensions compatible with translocation through dilated Pd (22,23,53). The coat protein (CP) of TMV is dispensable for cell-to-cell movement (26,96), which is consistent with the transport of viral RNA (vRNA) in a nonencapsidated form (39).…”
mentioning
confidence: 99%
“…Like other plant viruses, TMV encodes a movement protein (MP) that interacts with Pd and facilitates the intercellular passage of its genome (28,39,64). The MP modulates the size-exclusion limit (SEL) of the Pd (107) and also binds single-stranded nucleic acids in vitro to form an unfolded, elongated ribonucleoprotein complex with apparent dimensions compatible with translocation through dilated Pd (22,23,53). The coat protein (CP) of TMV is dispensable for cell-to-cell movement (26,96), which is consistent with the transport of viral RNA (vRNA) in a nonencapsidated form (39).…”
mentioning
confidence: 99%
“…TMV MP specifically accumulates in PD and modifies the plasmodesmatal size exclusion limit in mature source leaves or tissues (Wolf et al, 1989;Deom et al, 1990;Ding et al, 1992). TMV MP and viral genomic RNA form a mobile ribonucleoprotein complex that is essential for cell-to-cell movement of viral infection (Watanabe et al, 1984;Deom et al, 1987;Citovsky et al, 1990Citovsky et al, , 1992Kiselyova et al, 2001;Kawakami et al, 2004;Waigmann et al, 2007). TMV MP also enhances intercellular RNA silencing (Vogler et al, 2008) and affects viral symptom development, host range, and host susceptibility to virus (Dardick et al, 2000;Bazzini et al, 2007).…”
mentioning
confidence: 99%
“…Atomic force microscopy has shown that naked TMV RNA is more compact, at about 4.3 nt nm 21 (Drygin et al, 1998;Kiselyova et al, 2001). Increased secondary structure formation would compact the RNA further.…”
mentioning
confidence: 99%